EFEKTIVITAS KEBIJAKAN PENGURANGAN PENGGUNAAN KANTONG PLASTIK DI DIVA SWALAYAN KRAKSAAN BERDASARKAN PERSPEKTIF MANAJEMEN - Pradani, Rizki Febri Eka; Putri, Sephia Eka Amalia (Politeknik Bisnis Indonesia, 2025)
This study discusses the implementation of green marketing at Diva Swalayan Kraksaan, particularly in response to the government regulation concerning the reduction of single-use plastic. The objective of this study is to examine how green marketing principles are applied through the green marketing mix elements: product, price, place, promotion, people, physical evidence, and process. The research uses a qualitative phenomenological approach, with data collected through interviews, observation, and documentation. The findings reveal that Diva Swalayan has implemented the paid plastic bag policy and provides reusable shopping bags as a form of environmental commitment. However, most products sold are not environmentally friendly. The initiative is mainly driven by local government regulation (Perbup No. 51 of 2023), not internal motivation. The initial phase faced resistance from consumers due to a lack of awareness, but after two months, acceptance improved. The promotion was limited and temporary, and public understanding remains a major barrier. Overall, the implementation shows initial progress, but greater efforts are needed in consumer education and consistent communication to achieve sustainable behavioral change.